TRANSPARANSI DAN PELAPORAN KEUANGAN LEMBAGA ZAKAT (UIN Sunan Kudus, 2017)
BAZNAS has now transformed into a large and influential zakah institution in the life of Indonesian society due to the power of the Law that shelter it. This is an institution awaited by Muslims in general. This institution is the Shariah institution authorized entitled to receive and distribution of zakat, infaq and alms. Therefore this institution should be established by each region throughout Indonesia both at provincial and district levels. Therefore, transparency becomes crucial because of the many parties who are interested in zakah institutions. Transparency can be done by presenting reasonable financial statements. The organizers of zakat institutions should be obliged to understand the preparation of financial statements. This is in some areas are still frequent inequality and lack of understanding of the basics in the preparation of zakah institutional financial statements.